2020
DOI: 10.1364/oe.405864
|View full text |Cite
|
Sign up to set email alerts
|

Passive photonic integration of lattice filters for waveguide-enhanced Raman spectroscopy

Abstract: To perform waveguide-enhanced Raman spectroscopy (WERS) or fluorescence spectroscopy in a compact device, the optical fibers to couple the passive photonic circuit to the laser source and detector require attachment directly to the die. This necessitates the integration of edge couplers and waveguide-based filters to isolate the fiber background emission from the on-chip signal, while efficiently coupling the pump laser and detector to the input and output fibers, respectively. In this work, we experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Of course, integration of additional components of a WERS system (source, filters, waveguides, and spectrometer) may be considered. For example, Tyndall et al [ 64 ] demonstrated the successful integration of an on-chip filter for WERS to get rid of the pump laser before spectrum collection. The cascaded Mach–Zehnder interferometer lattice filter blocked 75% of the power at the notch wavelength and maintained >90% transmission for wavelengths outside the filter notch.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, integration of additional components of a WERS system (source, filters, waveguides, and spectrometer) may be considered. For example, Tyndall et al [ 64 ] demonstrated the successful integration of an on-chip filter for WERS to get rid of the pump laser before spectrum collection. The cascaded Mach–Zehnder interferometer lattice filter blocked 75% of the power at the notch wavelength and maintained >90% transmission for wavelengths outside the filter notch.…”
Section: Discussionmentioning
confidence: 99%
“…Background emission from the Si 3 N 4 waveguides was considered the fundamental limitation to SNR and the MMI is expected to contribute a lower background due to its shorter length. Tyndall et al 157 integrated directional coupler lattice filters for Si 3 N 4 WERS in a forward-and backscattering configuration, showing significant reduction in collected input fiber background and collected pump, the latter important for reducing output fiber background.…”
Section: ■ Review Of Recent Wers Implementationsmentioning
confidence: 99%
“…In return, the forward-scattered light collection efficiency generally has a maximum for a particular waveguide length, beyond which the propagation loss dominates, thus reducing the collected signal power (Figure 4c). A different approach to eliminating the influence of the background has been to integrate edge couplers and waveguide filters onto the chips, as demonstrated by Tyndall et al [204,206] (Figure 4d). An array of polarization maintaining single-mode fibers is aligned directly to the waveguide facets through edge couplers; the subsequent use of lattice filters helped in separating the background and collecting both the forward-and backward-propagated Raman scattered light at separate outputs.…”
Section: Configuration and Integrationmentioning
confidence: 99%